2015
DOI: 10.1001/jamadermatol.2014.5254
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Primary Nonadherence to Acne Treatment

Abstract: Primary adherence to an acne treatment regimen is better when only 1 treatment is prescribed. Some patients may not complete acne treatment because 1 or more of their medications were never obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…Similar to Anderson et al, 15 we found a decrease in primary nonadherence to dermatologic medication with use of e-prescriptions. We also found that, during the first 4 days from the index visit, patients with paper prescriptions had a higher rate of full adherence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to Anderson et al, 15 we found a decrease in primary nonadherence to dermatologic medication with use of e-prescriptions. We also found that, during the first 4 days from the index visit, patients with paper prescriptions had a higher rate of full adherence.…”
Section: Discussionsupporting
confidence: 90%
“…In dermatology, only a few, mostly small studies have specifically investigated primary nonadherence. [15][16][17] In this study, we measure primary nonadherence to dermatologic medications by examining prescription data from a large, urban county hospital system with an enclosed prescription environment. Patient and prescription characteristics were evaluated to assess factors associated with primary nonadherence.…”
mentioning
confidence: 99%
“…However, topical retinoids require repeated applications (once or twice daily for at least 3 months) and are burdened by several side‐effects, such as redness, sensitivity and dry skin. Those side‐effects together with the prolonged duration of therapy are responsible for the reduced compliance towards this kind of treatment …”
Section: Resultsmentioning
confidence: 99%
“…Those side-effects together with the prolonged duration of therapy are responsible for the reduced compliance towards this kind of treatment. 32 The largest study available regarding treatment options for FRD describes the efficacy of superpulsed carbon dioxide laser treatment in a cohort of 50 patients affected by FRD. 33 Laser vaporization of the epidermis was followed by extraction of Table 3 Local complication rate (expressed as percentage), with 95% CI, in the individual studies included in the meta-analysis.…”
Section: Treatmentmentioning
confidence: 99%
“…Studies have shown that prescription of a single product might improve compliance with acne treatment. [1520]…”
Section: Discussionmentioning
confidence: 99%